2016
DOI: 10.1002/2015gl067487
|View full text |Cite
|
Sign up to set email alerts
|

The vertical propagation of disturbances triggered by seismic waves of the 11 March 2011 M9.0 Tohoku earthquake over Taiwan

Abstract: In this paper, concurrent/colocated measurements of seismometers, infrasonic systems, magnetometers, HF‐CW (high frequency‐continuous wave) Doppler sounding systems, and GPS receivers are employed to detect disturbances triggered by seismic waves of the 11 March 2011 M9.0 Tohoku earthquake. No time delay between colocated infrasonic (i.e., super long acoustic) waves and seismic waves indicates that the triggered acoustic and/or gravity waves in the atmosphere (or seismo‐traveling atmospheric disturbances, STAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 28 publications
2
74
0
1
Order By: Relevance
“…Similar shapes of wave packets and frequency contents of v z and w (f D ) fluctuations were also observed for the 2015 Nepal earthquake by the CDSS in the Czech Republic and Taiwan [Chum et al, 2016]. Liu et al [2016] used collocated measurements by seismometers, infrasound sensors, magnetometers, continuous Doppler sounding, and dual-frequency GPS receivers in Taiwan to demonstrate that the time delays between observations of coseismic disturbances at various heights are consistent with the vertically propagating infrasound waves generated locally in Taiwan by the vertical component of seismic waves triggered by the 2011 Tohoku earthquake. The coseismic perturbations caused by vertically propagating infrasound waves were also confirmed by independent sounding techniques; Maruyama and Shinagawa [2014] showed that the disturbances observed in the ionograms are consistent with the ionospheric perturbations generated by the vertically propagating infrasound.…”
Section: Discussionsupporting
confidence: 68%
“…Similar shapes of wave packets and frequency contents of v z and w (f D ) fluctuations were also observed for the 2015 Nepal earthquake by the CDSS in the Czech Republic and Taiwan [Chum et al, 2016]. Liu et al [2016] used collocated measurements by seismometers, infrasound sensors, magnetometers, continuous Doppler sounding, and dual-frequency GPS receivers in Taiwan to demonstrate that the time delays between observations of coseismic disturbances at various heights are consistent with the vertically propagating infrasound waves generated locally in Taiwan by the vertical component of seismic waves triggered by the 2011 Tohoku earthquake. The coseismic perturbations caused by vertically propagating infrasound waves were also confirmed by independent sounding techniques; Maruyama and Shinagawa [2014] showed that the disturbances observed in the ionograms are consistent with the ionospheric perturbations generated by the vertically propagating infrasound.…”
Section: Discussionsupporting
confidence: 68%
“…The data are designed for monitoring the ionospheric space weather and also for detecting precursors (i.e., SIPs) and co-seismic disturbances (i.e., seismotraveling ionospheric disturbances) induced by worldwide earthquakes (cf. Liu et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the long lasting co-seismic pulsations appearing at the CC station might be due to the ground water and underground structure around Meishan fault being complex (Yen et al 2008;Ching et al 2011;Wilcox et al 2011). By contrast, researchers (Iyemori et al 2005;Hao et al 2013;Yen et al 2015;Liu et al 2016a) observe that seismo-magnetic pulsations with much longer period (low frequency) constantly lag seismic wave pulses by about 200+ minutes, suggesting that ionospheric conductivity affects magnetic fields. Since there is almost no time lag between magnetic pulsations and seismic waves at each co-located station, the co-seismo magnetic pulsation is unlikely related to the ionospheric conductivity.…”
Section: Experiments Setup and Observationmentioning
confidence: 95%
“…6). Liu et al (2016a) study the vertical propagation of disturbances triggered by seismic waves of the 11 March 2011 M 9.0 Tohoku earthquake over Taiwan. However, they find that there is no time lag between co-seismic infrasound fluctuations and the colocated seismic waves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation